PENINGKATAN KEMAMPUAN GURU DALAM MENDESAIN EDUGAMES PADA PEMBELAJARAN MATEMATIKA SD - Yullys Helsa; Yetti Ariani; Melva Zainil Zainil; Risda Amini (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
With the development of technology in the 21st century it has been able to provide pro-active learning, easy to understand and comprehensive as a learning environment, so it needs to be created IT-based learning media, namely edugames to help the learning process in elementary schools. The problem encountered in this study is that a small portion of teachers do not understand how to design edugames learning. The purpose of this study is to improve the ability of teachers to design edugames learning in mathematics learning. The type of research used is development using the Plomp model. The subjects in this study were teachers of Bukittingi City 02 Pilot School. The instrument in this study was edugames learning media. This research produces edugames media in the learning process created by the teacher